TRADITIONS OF KINDERGARTENS ABROAD - G'aniyeva, Hayriniso (Maktabgacha taʼlim jurnali, 2023)
In this article, the traditions of preschool educational institutions in foreign countries are studied on the basis of comparative analysis. Mainly information about the forms and conditions of pre-school education in developed Western and Eastern countries is given. Also, special attention is paid to the research conducted in connection with the study of foreign experiences related to preschool education and upbringing.